Differential Expression of Newly Identified Long Intergenic Non‐Coding RNAs in Buffalo Oocytes Indicating Their Possible Role in Maturation and Embryonic Development. Issue 7 (11th January 2017) - Dholpuria, Sunny; Kumar, Manish; Kumar, Sandeep; Sarwalia, Parul; Rajput, Sandeep; Kumar, Rakesh; De, Sachinandan; Datta, Tirtha K.
ABSTRACT: Female germ cell and its intricate milieu regulate key processes of folliculogenesis and early embryonic development. However, the composition and dynamics of the oocyte transcriptome defines its future fertilizing ability which in turn depends on a number of oocyte specific genes whose identities are still unknown. In this context, the construction of buffalo oocyte specific subtracted cDNA library has raised fresh challenges of defining the importance of a battery of oocyte expressed transcripts in oocyte maturation. The present study tried to characterize these hitherto unknown transcripts and further to assess their expression dynamics in buffalo oocytes of different quality. For this purpose, three ESTs were selected from the library and subjected to 5′ and 3′ RACE for generating their full length sequences. These constructed full length sequences were validated by amplifying them in oocytes. Further these sequences were extensively analyzed for their coding potential and possible role using coding potential calculator and miRNA database. Besides, their expression was monitored during in vitro maturation in good (BCB+) and poor quality (BCB−) oocytes which was interestingly found to be differing significantly. All the three sequences under study were interpreted as long intergenic non‐coding RNAs with the possibility of two of them acting as a miRNA precursors. Also, their differential expression trends in competitively diverse oocytes hints at their possible involvement in oocyte maturation and future embryonic development which needs to be explored further. J. Cell. Biochem. 118: 1712–1721, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Described new non coding RNAs which could be important for deciding the development ability of buffalo oocytes. These intergenic sequences were demonstrated to have no coding potential, yet observed to be a potential precursor of other classes of miRNAs having role in cell regulation important for the functioning of ovarian tissues.